Twisted "appendix epiploica" as extraordinary cause of discomfort at the right lower abdomen and rare differential diagnosis of acute appendicitis - a representative case. (November 2017) - Schäfer, Stefan; Garlipp, Benjamin; Wex, Cora; Häusler, Inken; Arndt, Stephan; Friebe, Björn; Jechorek, Dörthe; Meyer, Frank
Abstract : Introduction: Appendicitis can be considered the most frequent cause of discomfort at the right lower abdomen. Simultaneously, it is the most frequent indication for a surgical intervention. In addition, there is a broad spectrum of differential diagnoses, which can lead to a very challenging finding-specific management in good time as found out in the presented case. Case description: A 44-year old female patient was transfered to the surgical department because of discomfort of the right lower abdomen with changing intensity which had persisted since the day before. Patient showed a reduced but stable clinical status (normosomic nutritional status; no relevant accompanying diseases). Previous oral nutrition was normal. Clinical examination revealed pain by palpation at the right lower abdomen. Laboratory parameters: White blood cell count, 8.2Gpt/L; CrP, 10.4mg/L; urine with no pathological finding; no increased serum β-HCG level. Transabdominal ultrasound as orienting initial imaging detected free fluid around the cecum and along the right iliac vessels (appendiceal diameter, approximately 6.5mm) – in summary, no sign of appendicitis with certainty. Because of a persisting symptomatology, indication for a surgical intervention was derived (intraoperatively, laparoscopic appendectomy and partial resection of the greater omentum). Postoperative course was uneventful (no general/specific complications, wound healing was properly, initiation of oral nutrition and mobilization were well tolerated). Pathohistological investigation revealed lipofibromatosis of the appendage of the cecum with attached necrotic fat tissue and hemostasis, which can be associated with the diagnosis of a twisted appendix epiploica (no hint for malignant tumor growth). Results and Conclusions: The finding as presented occurs very rarely (approximately, 0.2%), which was initially misinterpreted as appendicitis with regard to symptomatology, ultrasound and laboratory findings. A definite diagnosis became only possible during the postoperative course by pathohistological investigation (suspicion already raised by intraoperative inspection aspects). Taking the final diagnosis into account, the question of a necessary indication for surgical intervention can be brought up, which can not be circumvented in case of unclear findings and medical history according to the surgical policy ("case of doubt"). However, as a consequence a more intense and extended diagnostic including a well developed clinical experience level as well as the clinical suspicion can be derived and concluded. This was an exciting and instructive case from a didactic point of view (relevant also for medical students) with rare occurrence in daily clinical practice, which includes the whole spectrum of differential diagnoses of i) unclear discomfort at the right lower abdomen in general and ii) acute appendicitis specifically.